Pengembangan Media Augmented Reality untuk Mereduksi Miskonsepsi Listrik dan Magnet Siswa Kelas V SD: Development of Augmented Reality Media to Reduce Misconceptions about Electricity and Magnetism among Fifth-Grade Elementary School Students - Juwita Rahayuningtyas; Subuh Anggoro (ITScience (Information Technology and Science), 2026)
Misconceptions regarding electricity and magnetism persist among fifth-grade students because concepts such as magnetic fields, electrical circuits, and electromagnets are abstract. This study aimed to develop Augmented Reality media based on Assemblr Edu, assess its feasibility, and obtain preliminary indications of its potential to reduce student misconceptions. The study employed a research and development method using the ADDIE model (analysis, design, development, implementation, and evaluation). A pre-experimental one-group pretest-posttest design was used, without a control group. The subjects consisted of 10 students for the limited trial and 24 students for the extensive trial. Data were collected through observation, expert validation questionnaires, and a three-tier test, then analysed using descriptive statistics, the Shapiro-Wilk normality test, and N-Gain analysis. Expert validation scores reached 83.3% for subject matter, 81.25% for language, and 91.25% for media, resulting in an average of 85.27%, which falls into the